Patterns of care for renal surgery: Underutilization of nephron-sparing procedures - Hammett, Jessica; Ko, Joan; Byrd, Nora; Crispen, Paul L.; Krupski, Tracey L. (Canadian Urological Association Journal, 2013)
Background: Nephron-sparing procedures are well-described, provide similar oncologic outcomes to nephrectomy, and potentially decrease morbidity as compared to nephrectomy. Methods: We analyzed academic and community health system data from Virginia and Kentucky to evaluate the utilization and cost of nephron-sparing procedures. Primary International Classification of Disease (ICD-9) diagnosis and procedure codes were employed to target subjects of interest. Results: In total, we analyzed 3809 subjects from Virginia and 3163 subjects from Kentucky between 2004 and 2009 who underwent treatment of a malignant renal mass. There has been a 6.1% and 14.8% decrease in nephrectomy utilization in Virginia and Kentucky, respectively, since 2004. In 2009, 71.4% and 68.8% of all procedures for the treatment of renal masses were radical nephrectomies. The proportion of nephron-sparing procedures has increased in academic (20%) and community (15%) health systems since 2004. The difference in cost between nephrectomy, partial nephrectomy and ablative therapy in Virginia and Kentucky hospitals was negligible (p > 0.05). Conclusions: Nephron-sparing procedures have been increasingly employed over the last 6 years, but are still underutilized. There does not appear to be a significant cost difference in the treatment of renal masses with nephrectomy, partial nephrectomy or ablative therapies.